2015
DOI: 10.1007/s12029-015-9790-4
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Study of Capecitabine in Substitution of 5-FU in the Chemoradiotherapy Regimen for Patients with Localized Squamous Cell Carcinoma of the Anal Canal

Abstract: Capecitabine can safely substitute infusional 5-FU in the standard chemoradiation regimen for SCC of the anal cancer, with a locoregional control of 86% in 6 months (CI 95% 0.72-0.94).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 22 publications
1
30
0
6
Order By: Relevance
“…From the remaining 158 studies, 152 were excluded as shown in Figure 1. Six trials met the predefined criteria [19, 2428]; however, patients from the phase-I trial by Deenen et al [24] were also included in the analysis of Meulendijks’s retrospective trial [28], and for this reason, the former was excluded. Five trials were included in the pooled analysis, totalling 218 patients [19, 2528].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…From the remaining 158 studies, 152 were excluded as shown in Figure 1. Six trials met the predefined criteria [19, 2428]; however, patients from the phase-I trial by Deenen et al [24] were also included in the analysis of Meulendijks’s retrospective trial [28], and for this reason, the former was excluded. Five trials were included in the pooled analysis, totalling 218 patients [19, 2528].…”
Section: Resultsmentioning
confidence: 99%
“…There were two phase-II trials [19, 25], both open-label prospective single-arm studies, and three retrospective studies, with one of them being a comparative study [28]. The number of patients per study ranged from 24 to 62, and the median follow-up periods ranged from 14 to 23 months.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations